1999
DOI: 10.1046/j.1365-2958.1999.01536.x
|View full text |Cite
|
Sign up to set email alerts
|

The periplasmic domain of the histidine autokinase CitA functions as a highly specific citrate receptor

Abstract: SummaryThe two-component regulatory system CitA /CitB is essential for induction of the citrate fermentation genes in Klebsiella pneumoniae. CitA represents a membrane-bound sensor kinase consisting of a periplasmic domain¯anked by two transmembrane helices, a linker domain and the conserved kinase or transmitter domain. A fusion protein (MalE±CitAC) composed of the maltose-binding protein and the CitA kinase domain (amino acids 327±547) showed constitutive autokinase activity and transferred the g-phosphate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
114
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 54 publications
2
114
0
1
Order By: Relevance
“…The periplasmic detector region of the sensors PhoQ of Salmonella typhimurium, CitA of Klebsiella pneumoniae, and DcuS of E. coli directly binds Mg 2ϩ , citrate, and fumarate, respectively (33)(34)(35). Here we showed that the periplasmic domain of the TorS sensor detects indirectly the presence of TMAO by binding the TorT-TMAO complex.…”
Section: Discussionmentioning
confidence: 75%
“…The periplasmic detector region of the sensors PhoQ of Salmonella typhimurium, CitA of Klebsiella pneumoniae, and DcuS of E. coli directly binds Mg 2ϩ , citrate, and fumarate, respectively (33)(34)(35). Here we showed that the periplasmic domain of the TorS sensor detects indirectly the presence of TMAO by binding the TorT-TMAO complex.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, even though sensor domains are expected to be functionally dimerized in situ on the membrane, they may exhibit quite low dimer affinity when isolated in solution. The E. coli PhoQ sensor domain has been shown to be monomeric in solution by analytical ultracentrifugation with a lower limit of 600 M measured for the K d of dimerization (12), and likewise both the CitA and DcuS sensor domains have also been reported to be mostly monomeric in solution (21,41). It follows that a certain lability may exist in the manner by which sensor domains self-associate, and therefore dimeric interactions within in a crystal-lattice environment may not necessarily be biologically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…The YufL/YufM TCS belongs to the CitA/ CitB family of TCSs. The members of this family that have already been characterized are CitA/CitB from E. coli (Kaspar & Bott, 2002) and Klebsiella pneumoniae (Bott et al, 1995;Kaspar et al, 1999), CitS/CitT from B. subtilis (Yamamoto et al, 2000) and Streptomyces coelicolor, YdbF/ YdbG from B. subtilis (Asai et al, 2000) and DcuS/DcuR from E. coli (Zientz et al, 1998;Golby et al, 1999). All these TCSs are involved in the control of genes required for TCA cycle intermediates import and utilization.…”
Section: Discussionmentioning
confidence: 99%